Partisan politics, divided government, and the economy - Alesina, Alberto 1957-2020; Rosenthal, Howard 1939-2022 (The political economy of institutions and decisions, 1995)
The authors first outline the rational partisan business cycle, where Republican administrations begin with recession, and Democratic administrations with expansions, and next the midterm cycle, where the President's party loses votes in the mid-term congressional election. The book argues that both cycles are the result of uncertainty about the outcome of presidential elections. Other topics covered include retrospective voting on the economy, coat-tails, and incumbency advantage. A final chapter shows how the analysis sheds light on the economies and political processes of other industrial democracies